Longitudinal physical performance and blood pressure changes in older women: Findings form the women's health initiative. (January 2022) - Laddu, Deepika R.; LaMonte, Michael J.; Haring, Bernhard; Kim, Hajwa; Cawthon, Peggy; Bea, Jennifer W.; Banack, Hailey; Cauley, Jane A.; Allison, Matthew A.; Martin, Lisa Warsinger; LeBoff, Meryl S.; Stefanick, Marcia L.; et al.
Highlights: Factors contributing to changes in blood pressure (BP) during old age are not well understood. Higher grip strength was associated with higher systolic and diastolic BP. Greater chair stand or gait speed performance was positively associated with diastolic BP. CVD history, antihypertensive medication use, and age may influence the longitudinal relationship between physical performance and BP. More research is needed to better understand clinical impact of physical performance on BP during aging. Abstract: Background: This study evaluated the association between changes in physical performance and blood pressure (BP) (e.g., systolic [SBP], diastolic [DBP], pulse pressure) in older women. Methods: 5627 women (mean age 69.8 ± 3.7 y) with grip strength, chair stand, gait speed performance and clinic-measured BP at baseline and at least one follow-up (years 1, 3 or 6) were included. Generalized estimating equation analysis of multivariable models with standardized point estimates described the longitudinal association between physical performance and BP changes in the overall cohort, and in models stratified by baseline cardiovascular disease (CVD), time-varying antihypertensive medication use (none, ≥1) and enrollment age (65–69 y; 70–79 y). Results: Overall, each z-score unit increment in grip strength was associated with 0.59 mmHg (95% CI 0.10, 1.08) higher SBP, and 0.39 mmHg (95% CI 0.11, 0.67) higher DBP. In stratified models, a standardized increment in grip strength was associated with higher SBP in women without CVD (0.81; 95% CI 0.23–1.39), among antihypertensive medication users (0.93; 95% CI 0.44, 1.41) and non-users (0.37; 95% CI 0.03, 0.71), and in those aged 65–69 y (0.64; 95% CI 0.04, 1.24). Similarly, a standardized increment in any of the three performance measures was associated with modestly higher DBP in antihypertensive medication users, and those aged 70–79 y. Associations between any performance measure and pulse pressure change were not significant. Conclusion: These results suggest a positive, and statistically significant relationship between physical performance and BP that appears to be influenced by CVD history, antihypertensive medication use, and age.